A comparison of non-vital bleaching techniques in the discolored tooth an in-vitro study - Vizcarra, Alexander; Estrella, Raymundo S.
Thirty-six upper anterior teeth with intact crowns were stained in-vitro, and then bleached under controlled conditions using the three commonly used bleaching techniques: the thermocatalytic, the walking bleach and the combination techniques. The teeth were evaluated using a standard shade guide for amount of color staining and bleaching. Results show that there is no significant difference between the bleaching efficacy of the three techniques. However, the walking bleach technique used significantly less procedural time than the other two techniques.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.